2020
DOI: 10.3390/diagnostics10080558
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Versus Iterative Reconstruction for CT Pulmonary Angiography in the Emergency Setting: Improved Image Quality and Reduced Radiation Dose

Abstract: To compare image quality and the radiation dose of computed tomography pulmonary angiography (CTPA) subjected to the first deep learning-based image reconstruction (DLR) (50%) algorithm, with images subjected to the hybrid-iterative reconstruction (IR) technique (50%). One hundred forty patients who underwent CTPA for suspected pulmonary embolism (PE) between 2018 and 2019 were retrospectively reviewed. Image quality was assessed quantitatively (image noise, signal-to-noise ratio (SNR), contrast-to-noise ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 35 publications
4
40
0
1
Order By: Relevance
“…However, many studies have shown that the potential dose reduction obtained with IR algorithms was limited to low contrast liver lesions and the outcomes found on phantoms overestimated the real dose reduction in patients (44)(45)(46). Nevertheless, the first patient studies published on pulmonary or cardiac CT angiography and chest and abdominal CT have also confirmed that AiCE improved both image quality and lesion detection as compared with AIDR 3D for a given dose level (22,25,26,30) or with a dose reduction (26,29,34,35). Singh et al found that the dose could be reduced by −84% between a standard protocol (CTDI vol : 13.0±4.4 mGy) with AIDR 3D and a low-dose protocol (CTDI vol : 2.1±0.8 mGy) with AiCE for the detection of the same abdominal lesions and an overall image quality scored acceptable for more than 95% of patients (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many studies have shown that the potential dose reduction obtained with IR algorithms was limited to low contrast liver lesions and the outcomes found on phantoms overestimated the real dose reduction in patients (44)(45)(46). Nevertheless, the first patient studies published on pulmonary or cardiac CT angiography and chest and abdominal CT have also confirmed that AiCE improved both image quality and lesion detection as compared with AIDR 3D for a given dose level (22,25,26,30) or with a dose reduction (26,29,34,35). Singh et al found that the dose could be reduced by −84% between a standard protocol (CTDI vol : 13.0±4.4 mGy) with AIDR 3D and a low-dose protocol (CTDI vol : 2.1±0.8 mGy) with AiCE for the detection of the same abdominal lesions and an overall image quality scored acceptable for more than 95% of patients (34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the TrueFidelity DNN was trained with both patient and phantom data whereas it was trained only with patient data for AiCE. CT images obtained with these algorithms using denoising techniques showed suppressed noise with no change of noise texture or distortion of anatomical and pathological structures (19,(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT difference between the hepatic artery and liver parenchyma in the arterial phase; CT difference between the abdominal aorta and the liver parenchyma in the arterial phase. Contrast-to-noise ratio (CNR) of the hepatic artery and abdominal aorta in the arterial phase, CNR=(CT (target vessel)-CT (same layer of the liver parenchyma))/SD (same layer of the liver parenchyma) 39 .…”
Section: Measurement and Calculation Of The Ct Datamentioning
confidence: 99%
“…During the process of the optimization of protection in medical imaging, the use of modern imaging systems and efficient reconstruction techniques is shown to be effective in order to reduce patient radiation dose. A deep learning reconstruction significantly reduced image noise and improved overall image quality of CT pulmonary angiography examinations in the emergency setting and offered an additional significant radiation dose reduction while allowing slices to be twice as thin as compared to hybrid iterative reconstruction (IR) [ 2 ]. The use of an Advanced Modeled IR (ADMIRE; Siemens Healthineers, Forchheim, Germany) allowed a reduction in the radiation dose to 25% of the original dose with the same diagnostic accuracy for the assessment of neck abscesses [ 3 ].…”
mentioning
confidence: 99%